FRI0113 THE BASELINE SOLUBLE GP130 IS ASSOCIATED WITH THE RESPONSE OF RHEUMATOID ARTHRITIS PATIENTS TO SARILUMAB. (2nd June 2020) - Yoshikawa, T.; Furukawa, T.; Tamura, M.; Hashimoto, T.; Morimoto, M.; Azuma, N.; Matsui, K.
Abstract : Background: IL-6 contributes significantly to the chronic inflammatory process of rheumatoid arthritis (RA). Sarilumab (SRL), a human anti-human IL-6 receptor alpha monoclonal antibody that blocks the signaling originated by the IL-6/IL-6R complex like tocilizumab, is an effective treatment. However, predictors of the response to sarilumab are still required. Objectives: We aimed to combine IL-6, soluble IL-6R (sIL-6R) and gp130 (sgp130) levels to identify groups of sarilumab responses. Methods: This research is a retrospective study. a total of 32 RA patients with SRL therapy in our department from February 1 in 2018 to December 31 in 2019 were included. Serum and clinical data from 32 RA patients were collected before treatment and until the last visit. Follow-up period was up to one year after starting SRL treatment. Serum were tested for IL-6 (Human IL-6 Quantikine ELISA Kit, R&D systems), sIL-6R (Human soluble IL-6R alpha Quantikine ELISA Kit, R&D systems) and sgp130 (Human soluble gp130 Quantikine ELISA Kit, R&D systems), using specific ELISAs according to the manufacturer's instructions. Hierarchical cluster analysis (JMP14.3.0) was used to establish the relationship between IL-6, sIL-6R and sgp130. We evaluated the efficacy of SRL treatment on the last visit using European League Against Rheumatism (EULAR) response criteria in the groups of patients. The other statistical analyses were performed with EZR 1.41, and p Values less than 0.05 were considered significant. Results: The median age of patients was 70.5 (IQR: 66.5-74.3) years and the median of disease duration was 7.3 (1.7-15.3) years. Nine (28.1%) patients were biologics and Jakinibs naive. the median follow-up periods were 24 (12-26) weeks. The baseline DAS28 was median 4.39 (3.77 - 5.43), and CDAI was 21.1 (11.7-29.5). When comparing responders and non-responders, there were no significant differences in any of the baseline parameters and cytokines. Four statistical significant clusters of RA patients (i.e., Group1, Group2, Group3 and tocilizumab use group before SRL) were defined by serum concentrations of IL-6, sIL-6R and spg130 at baseline. The levels of IL-6 expressed as median in Group1 patients were 25.6 (14.4–72.2) pg/ml, in Group2 5.9 (3.3–11.3) pg/ml, and in Group3 70.2 (45.4–86.1) pg/ml (p < 0.002, significant difference only between Group2 and Group3). The levels of sIL-6R expressed as median in Group1 patients were 38.7 (34.7-45.1) ng/ml, in Group2 35.1 (24.8-41.9) ng/ml, and in Group3 35.7 (34.2-39.8) ng/ml (p = 0.5477). The levels of sgp130 expressed as median in Group1 patients were 272.6 (263.0-277.2) ng/ml, in Group2 223.1 (221.0-228.0) ng/ml, and in Group3 204.6 (192.0-207.6) ng/ml (p < 0.00003, significant difference between the three groups respectively). There were no significant differences in any of the baseline clinical features and laboratory findings between the three groups. Out of the 8 patients in Group1 had a good or moderate response to SRL. Conversely, the percentage of patients with no response to SRL was higher in Group3 than in Group1 and Group2. Conclusion: RA patients could be easily stratified prior to the rapeutic intervention with sgp130 related to the IL-6 signal reguration. Group1 patients, who had the best response to SRL, had the highest level of sgp130. Disclosure of Interests: Takahiro Yoshikawa: None declared, Tetsuya Furukawa: None declared, Masao Tamura: None declared, Teppei Hashimoto: None declared, Mai Morimoto: None declared, Naoto Azuma: None declared, Kiyoshi Matsui Grant/research support from: Asahi Kasei Pharma, Astellas Pharma (research grants), Speakers bureau: Bristol-Myers Squibb (lecture fees)